2014
DOI: 10.1002/hrm.21580
|View full text |Cite
|
Sign up to set email alerts
|

How Does Relative Deprivation Influence Employee Intention to Leave a Merged Company? The Role of Organizational Identification

Abstract: Recognizing the importance of postmerger integration from a human resource management perspective, this study explores the relationship between employee perceptions of relative deprivation during a merger and acquisition (M&A) process and their turnover intentions. Drawing on social identity theory, we investigate whether the relationship between relative deprivation and turnover intention can be mediated by employee organizational identification. The results, based on a two‐phase survey of 222 employees in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 94 publications
(113 reference statements)
1
39
0
Order By: Relevance
“…Thus, organizational identification has showed its potential capacity to reduce employee turnover intention (He & Brown, 2013;Riketta, 2005;. Previous individual empirical studies have widely confirmed the significant relationship between organizational identification and turnover intention in different context (Akgunduz & Bardakoglu, 2015;Cho et al, 2014;Cole & Bruch, 2006;De Moura et al, 2009;Fallatah et al, 2017;Kumar Mishra & Bhatnagar, 2010;. "Rural migrant workers" are identified by the household registration system and land contract system, they work in non-agricultural sectors, but still hold rural resident identification (Li & Li, 2007).…”
Section: Organizational Identification and Turnover Intentionmentioning
confidence: 99%
“…Thus, organizational identification has showed its potential capacity to reduce employee turnover intention (He & Brown, 2013;Riketta, 2005;. Previous individual empirical studies have widely confirmed the significant relationship between organizational identification and turnover intention in different context (Akgunduz & Bardakoglu, 2015;Cho et al, 2014;Cole & Bruch, 2006;De Moura et al, 2009;Fallatah et al, 2017;Kumar Mishra & Bhatnagar, 2010;. "Rural migrant workers" are identified by the household registration system and land contract system, they work in non-agricultural sectors, but still hold rural resident identification (Li & Li, 2007).…”
Section: Organizational Identification and Turnover Intentionmentioning
confidence: 99%
“…Social identity theory in its meaning claims that every human being is defined by social relationships (Cho, et al, 2014;Ashforth & Mael, 1989;Van Knippenberg et al, 2007). The theory implies that an individual sees and defines him/herself to a certain extent or even completely as a part of a structured society, through group membership, or by subscribing to the values and meanings of a group, a society or an organization (Stets & Burke, 2000).…”
Section: Social Identity Theorymentioning
confidence: 99%
“…We measured respondents' relative deprivation using the five items developed by Tropp and Wright (1999), which have also been used in a recent study (Cho et al, 2014). Two of these items assess fraternal relative deprivation, and three items assess egoistic relative deprivation.…”
Section: Relative Deprivationmentioning
confidence: 99%